Engagement with life and psychological well-being in late adulthood: Findings from community-based programs in Portugal. - Alice Bastos; Joana Monteiro; Raquel Barbosa; Helena Pimentel; Sofia Silva; Carla Faria (PLoS ONE, 2023)
Objectives Human aging is a multidirectional, multidimensional, and multicausal process that reflects biological, psychological, and sociocultural influences, which act in distinct combinations throughout the life-span. Proactivity towards avoiding the usual aging process is needed. This study analyses the long-term effects of participation in Community-Based Programs on psychological well-being. Method A sample of 150 community-dwelling participants enrolled in Community-Based Programs, aged 55 to 84 years and living in three Portuguese localities were matched by age (55-64, 65-74, 75-84 years), gender, and locality with a comparison group of non-participants. We administered a multidimensional gerontological protocol which included socio-demographic information, measures of health/disease, functional ability, social network, cognitive performance and psychological well-being. Hierarchical regression models were used to test the effects of Community-Based Programs on psychological well-being adjusting for remaining variables. Results Overall, psychological well-being is positively associated with household income and satisfaction with health. Nevertheless, in participants, psychological well-being builds predominantly upon social network and is not associated with a moderate inability or cognitive deficits, contrasting with psychological well-being in non-participants. After adjusting for background variables, psychological well-being was positively associated with health satisfaction and social network and negatively related to moderate inability. Further, a significant interaction of participation in Community-Based Programs with age, points out higher levels of psychological well-being in participants contrasting with a downward trend in non-participants. After stratification by age, psychological well-being increases with time attending Community-Based Programs in the oldest (75-84 years) contrasting with the remainder. Conclusions Participation in Community-Based Programs may improve the negative effects of the aging process on psychological well-being. This positive effect as age increases may be linked to a reinforcement of social network, valued more by participants in Community-Based Programs. Furthermore, the programs may act as a healing/maintenance strategy in persons with moderate inability and/or cognitive deficits.